Biographies of a reformation religious change and confessional coexistence in Upper Lusatia, c. 1520-1635 - Christ, Martin 1991- (Studies in German history, 2021)
This volume introduces the region of Upper Lusatia, where Lutherans, Catholics and a range of other groups co-existed in a largely peaceful manner